2017
DOI: 10.1111/1755-5922.12242
|View full text |Cite
|
Sign up to set email alerts
|

The role of spironolactone on myocardial oxidative stress in rat model of streptozotocin‐induced diabetes

Abstract: The increase in total nitrite/nitrotyrosine in DM promoted significant compensatory increases in antioxidant activities of SOD, catalase and glutathione peroxidase/reductase probably to prevent cardiac oxidative damage. The use of spironolactone reduced nitrite generation and improved vitamin E levels independent of blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
(76 reference statements)
3
11
0
2
Order By: Relevance
“…In the cardiac tissue, similarly to the serum, the activity of antioxidative enzymes was elevated. These results are in line with some other reports [26,61], but there are also reports indicating a decrease in antioxidative enzymes activity in the heart of diabetic animals [24,33,58,62]. In the study conducted by Okutan et al regarding the effect of caffeic acid phenethyl ester on oxidative stress markers in the heart it was shown that similarly to our results, the activities of SOD and CAT were elevated in diabetic rats, while GPx activity was unchanged when compared to the non-diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the cardiac tissue, similarly to the serum, the activity of antioxidative enzymes was elevated. These results are in line with some other reports [26,61], but there are also reports indicating a decrease in antioxidative enzymes activity in the heart of diabetic animals [24,33,58,62]. In the study conducted by Okutan et al regarding the effect of caffeic acid phenethyl ester on oxidative stress markers in the heart it was shown that similarly to our results, the activities of SOD and CAT were elevated in diabetic rats, while GPx activity was unchanged when compared to the non-diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it can be concluded, that the model reflecting the changes observed in the type 2 diabetes in humans in the most adequate manner is a model in which a high-fat diet is combined with a single injection of a low dose of streptozotocin [52,53]. It should be noted that the majority of studies describing the effect of tested substances on parameters affected by both the type 1 and type 2 diabetes is based on the experiments conducted on male laboratory animals [17,[19][20][21][22][23][24][25][32][33][34][35]37,38,50,51,[54][55][56][57][58][59][60][61][62]. Following the suggestion of The National Institutes of Health (NIH) to use female animals in the laboratory studies [63] and reports about sex-dependent metabolic differences [64,65], our experiment was conducted on female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, DM type 2 affects 347 million worldwide [1], while the risk of mortality is 1.7 times higher in patients with diabetes mellitus than in the non-diabetic population [2]. Inflammation, neurohumoral activation and structural remodelling are multiple mechanisms that contribute to cardiovascular disease, whereby one of the primary means contributing to CVD development is oxidative stress [3].…”
Section: Introductionmentioning
confidence: 99%
“…Increased bioavailability of reactive oxygen species (ROS) is defined as oxidative stress and is noticed in type 2 DM and reduced antioxidant enzymes expression/activity [3]. One of the many mechanisms correlated with vascular damage induced by oxidative stress is decreased nitric oxide (NO) bioavailability.…”
Section: Introductionmentioning
confidence: 99%